Effect of feeding fresh and frozen rumen fluid on the growth performance of goat kids. Issue 4 (3rd April 2022) - R, Tamilinban; Vanan, Thanga.Thamil; T, Sivakumar; R, Karunakaran; P, Tensing Gnanaraj
ABSTRACT: The effect of feeding fresh and frozen rumen fluid on the growth performance was studied in Tellicherry goat kids at Instructional Livestock Farm Complex (ILFC), TANUVAS, Chennai by assessing body weight and average daily gain. Twenty four numbers of Tellicherry goat kids of both sexes at 15 days of age were selected and allotted randomly to the following three treatment groups viz ., T1, T2 and T3 equally of eight kids per group. Treatment T2 and T3 were fed with 100 ml fresh and frozen rumen fluid, respectively, once in 3 days for 120 days whereas kids in T1 were treated as control. The final body weight (Kg) and average daily gain (g) recorded in T1, T2 and T3 were 9.57 ± 0.33 and 61.19 ± 3.59, 10.79 ± 0.23 and 72.14 ± 2.90 and 10.69 ± 0.16 and 70.95 ± 1.69, respectively. Kids in the treatment groups T2 and T3 attained significantly (P < 0.01) higher final body weight and higher average daily gain than T1 . The results of the study revealed that feeding either fresh or frozen rumen fluid had resulted in improved growth performance.